IMPLICATIONS OF COMMUNITY'S UNDERSTANDING OF MEDICAL MALPRACTICES IN RELATION TO THE ASPIRATIONS OF FAIR HANDLING OF MEDICAL MALPRACTICE VICTIMS - Ali Fuad Hasyim (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Its activities provide knowledge and understanding to the public so that they know in detail that every citizen is protected by their rights by the constitution. The right to defend life and life can be interpreted that everyone has the same right to defend his life. One of them is to get health services. Health services are carried out by professional health workers. Based on Law No. 36 of 2014 concerning Health Workers, it regulates the rights and obligations of health workers, while in Law No. 44 of 2009 concerning Hospitals there are rights and obligations of patients. Law No. 29 of 2004 concerning Medical Practice which stipulates that health workers in carrying out their profession are really required to have professional behavior. If cases of malpractice arise, it is hoped that the pattern of settlement of these cases to be more fair and dignified needs to be seen comprehensively. So that there will be no decision that only provides justice to one party while the other party (especially the victim) receives less attention. An alternative model for resolving medical malpractice cases based on a balance between professional duties and existing victims (patients). Medical personnel may not commit malpractice on purpose, where there is a possibility of negligence in carrying out their professional work according to existing operational standards. On the other hand, a patient's great trust in a doctor needs attention too. The settlement approach has been carried out by enforcing a code of ethics and professionally, there are advantages and disadvantages, on the basis of these considerations, an alternative solution is sought for the occurrence of malpractice in the medical field that can produce a balanced and fair decision. A law enforcement construction that is expected to provide justice for all parties. Socialization about the pattern of settlement in a just manner needs to be done to the community so that the community members are aware of the position and conditions that are manifested in their rights and obligations.